Der Ausdruck meleket haššāmayim in Jer 7,18-MT und Jer 44,17.18.19.25-MT und die unterschiedlichen Übersetzungen in der LXX - Vonach, Andreas (Protokolle zur Bibel, 2006)
The Hebrew expression meleket haššāmayim is translated as stratia tu uranu in Jer 7:18-LXX, but as basílissē tu uranu in Jer 51(44-MT):17.18.19.25-LXX. In this essay it is argued, that the reason for these different translations is neither found in the hebrew Vorlage of Jer-LXX, nor in various greek translaters of the book of Jeremiah. It more points to the translation-technique of the LXX-translators. The former word (Jer 7) is spoken to the people living in Judah, whereas the latter (Jer 51/44) adresses the Judaean people living in Egypt. This was a good opportunity for the translator to give his text also a current topic for his Alexandrian audience, which from time to time was quite prepared to take part at the feasts and the worshipping of goddess Isis. This thesis, that Jer 51-LXX is a good testcase for the translation-technique of giving the text also a current value, can moreover be beard out by the fact that the actions of women are more emphasized in Jer 51-LXX than in Jer 44-MT.